2017
DOI: 10.3892/etm.2017.4538
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA-605 promotes cell proliferation, migration and invasion in non-small cell lung cancer by directly targeting LATS2

Abstract: Abstract. Lung cancer is the most common cause of cancerassociated mortality for men and women worldwide. An increasing number of studies have reported that the abnormal expression of microRNAs contributes to the pathogenesis of the majority of human cancer types, including non-small cell lung cancer (NSCLC). The present study aimed to measure microRNA-650 (miR-650) expression in NSCLC and evaluate its function in NSCLC cells. Reverse transcription-quantitative polymerase chain reaction was used to determine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In this study, we observed that LATS2 is directly targeted by miR-650. A recent study involving NSCLC cells indicated that miR-650 promotes cell migration and invasion by targeting LATS2 [22]. Our in vitro and in vivo analyses support these published findings, while also demonstrating that LATS2 counteracts the effects of miR-650 on HCC cell proliferation, migration, and invasion.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we observed that LATS2 is directly targeted by miR-650. A recent study involving NSCLC cells indicated that miR-650 promotes cell migration and invasion by targeting LATS2 [22]. Our in vitro and in vivo analyses support these published findings, while also demonstrating that LATS2 counteracts the effects of miR-650 on HCC cell proliferation, migration, and invasion.…”
Section: Discussionsupporting
confidence: 81%
“…Tumor metastasis [ 157 ] miR-221/222 p27 / Kip1 Upregulated Regulate activation of cyclin E and cyclin D [ 158 ] Glioblastoma miR-124 CDK6 Upregulated Inhibit cell proliferation [ 159 ] miR-137 CDK6 Upregulated Inhibit cell proliferation [ 160 ] miR-128 BMI1 Upregulated Decreasing cell proliferation in IDH1 mutant glioma [ 161 ] miR-23b HMGA2 Upregulated Cell cycle arrest and proliferation inhibition [ 162 ] miR-125b CDK6, E2F3, CDC25A Downregulated Induce G1/S cell cycle arrest [ 163 ] miR-34 BCL2, NOTCH1 Downregulated Targeting p53. Anti-apoptotic, increase cell proliferation [ 164 ] Lung miR-605 LATS2 Upregulated Promote cell proliferation, migration and invasion [ 165 ] let-7 KRAS, MYC, CDK6 HMGA2, TGFBR2 Downregulated Suppression of multiple oncogenic...…”
Section: Mirnas and Cell Cycle Regulation Of Stem Cellsmentioning
confidence: 99%
“…Many of the miRNAs have previously been reported associated with genes or biological responses that could impact CRC. For instance, miR-590-5p, miR-106b, and miR-93 have been associated with PTEN in the PI3K/AKT pathway 34,35 ; miR-145 has been associated with cell-cycle related factors such as CDK4 and cyclin E2 36 ; miR-150 has been associated with immune response 37 and reducing inflammatory cytokine production 38 ; miR-17-5p has been shown to inhibit proliferation and trigger apoptosis 39 ; miR-199 has previously been associated with IKKB 40 and with ITGA3 41 ; miR-203 as being associated with BIRC5 which encodes survivin 42 ; miR-20 has previously been associated with cyclin D1 43 ; miR-221 has been reported as being associated with TNFα 40 ; miR-650 has been associated with BCL2 and AKT2 and has been shown to promote cell proliferation and invasion 44-46 . However, our findings add to the functional information we have for these miRNAs in that we observed their associations with genes not previously reported and with specific disease pathways.…”
Section: Determining Functionalitymentioning
confidence: 99%